Value of an unknownfactor: the work of a psychologist in health institutions - Guillén, Julio C. (2011)
The present communication is related to psychologist’s work in mental health institutions, particularly in the Medical Psychology Center as well as other teaching institutions as the university. In both cases, we will explain the psychologist‘s position within the institution and at the same time their relations with other professionals, patients or students. The question arises: Is it possible to characterize the position of a physichologist in the institution from a formal point of view, without stating at the same time and at the same movement? Even admitting that we have a certain knowledge, as it testifies a diploma, it is about asserting this knowledge, or positioning as “representatives” (faire-valoir) of a knowledge “other”? The clinical experience shows that university knowledge finds their limits in the particularity of each case. In such aspect, we come back to the modified previous question: The sui-generis articulation suggests that psychoanalysis among theory and practice will constitute our reference to answer this question. We will introduce the creation experience of a “clinical reflection group” in The Medical Psychology Center, finding and discarding of different professionals which interrogates particularly the psychologist’s position.